ORGANIZAÇÃO E FUNCIONAMENTO DAS UNIDADES GESTORAS DOS REGIMES PRÓPRIOS DE PREVIDÊNCIA SOCIAL DE MATO GROSSO DO SUL - ANNA KAROLINA GUIMARÃES MONTEIRO (2023)
Social security aims to guarantee means of subsistence to its beneficiaries, as a result of certain disabilities, retirement, imprisonment or death, having, therefore, great social and economic importance. It encompasses, together with social assistance and health, social security. The Brazilian social security system is structured through the social security general policy (Regime Geral de Previdência Social – RGPS, in portuguese), civil servants’ pension funds (Regime Próprio de Previdência Social – RPPS, in portuguese) and the supplementary pension fund (regime de previdência complementar – RPC, in portuguese). The RPPS is a public pension fund of institution optional by the entity, covering civil servants of effective position of the Union, States, Federal District and Municipalities, and administered by a management unit (unidade gestora – UG, in portuguese). The general objective of this research is to carry out a diagnosis of the existing civil servants’ pension funds in the State of Mato Grosso do Sul, as well as their management units. Information was obtained through an electronic questionnaire sent to the UG managers. Other data were extracted from the electronic addresses of the Secretariat of Social Security, the rendering of accounts sent to the State of Mato Grosso do Sul Audit Court, as well as the electronic addresses of the municipalities, the state and the UG. Among the results obtained, it is noteworthy that, despite the fact that most UGs are constituted by an indirect administration body, 30% of them do not have an accounting sector separate from the entity, and also about 30% of UGs have 1 or 2 employees in exclusive dedication, including the manager and/or directors. The majority (70.4%) of the UGs also stated that the positions of a permanent nature that work in the RPPS are not being filled through a public tender, causing a negative impact on management. In addition, 96% of the RPPS in Mato Grosso do Sul have an actuarial deficit and two have financial insufficiency, Campo Grande and the State of Mato Grosso do Sul. Also, an Action Plan was proposed by the State of Mato Grosso do Sul Audit Court to contribute to the improvement of the civil servants’ pension funds´ management units existing in the State of Mato Grosso do Sul.